(untitled) - Shapiro, Norman (Oxford, NY, 1998)
A comprehensive, flexible, and up-to-date vocabulary reference and teaching tool for English language learning. The Oxford Picture Dictionary and its components create a highly teachable programme that can be used as a complete, four-skills beginning course, or as a language development supplement and practical reference. NEW Grammar Activity Book
Keywords: English language,Picture dictionaries, English,Picture dictionaries, Vietnamese; Dictionaries,Vietnamese